Socioeconomic Position, Rural Residence, and Marginality Influences on Obesity Status in the Adult Mexican Population. (22nd May 2012) - Sparks, P. Johnelle; Sparks, Corey S.
Abstract : This paper assesses individual and social environment determinants of obesity in the adult Mexican population based on socioeconomic position, rural residence, and areal deprivation. Using a nationally representative health and nutrition survey, this analysis considers individual and structural determinants of obesity from a socioeconomic position and health disparities conceptual framework using multilevel logistic regression models. We find that more than thirty percent of Mexican adults were obese in 2006 and that the odds of being obese were strongly associated with an individual's socioeconomic position, gender, place of residence, and the level of marginalization (areal deprivation) in the place of residence. Surprisingly, areas of the country where areal deprivation was highest had lower risks of individual obesity outcomes. We suggest that programs oriented towards addressing the health benefits of traditional food systems over high-energy dense refined foods and sugary beverages be promoted as part of a public health program aimed at curbing the rising obesity prevalence in Mexico.